Nielsen realisation for untwisted automorphisms of right-angled Artin groups - Hensel, S; Kielak, D (Wiley, 2018)
We prove Nielsen realisation for finite subgroups of the groups of untwisted outer automorphisms of RAAGs in the following sense: given any graph $Γ$, and any finite group $G\leqslant U^0(A_Γ) \leqslant Out^0(A_Γ)$, we find a non-positively curved cube complex with fundamental group $A_Γ$ on which $G$ acts by isometries, realising the action on $A_Γ$.